Decentring the majority-minority paradigm: a multi-dimensional conceptualization of inter-ethnic relations based on a study of Chinese Canadians - Tsang, A. Ka Tat; Leung, Vivian W. Y.; Tan, Weijia; Chuang, Deng-Min; Hu, Ran (My University, 2022)
Inter-ethnic research has been dominated by studies on majority–minority relations. The limited studies on relations among ethnic minority groups are usually restricted to a focus on attitudes and the cognitive domain, with little attention to actual behaviours. As Canada becomes increasingly diverse, it calls for a greater need in examining the interpersonal relationships among ethnic minority groups. A study originally designed to look at intra-group dynamics generated results that led the authors to decentre the dominant majority–minority view and explore inter-ethnic engagements. This report examines the subjective sense-making, actual performance, and management of inter-ethnic relations from Chinese Canadians’ perspectives. Data from individual interviews and focus groups with thirty-five Chinese Canadians show a multidimensional picture: factors such as participants’ needs, circumstances, characteristics, and capacities play a more significant role in shaping relationship development and maintenance. Results also reveal the complex and contingent nature of the sense-making and management of inter-ethnic relationships. These findings call for a more holistic view of individuals’ experiences that include cognitive, affective, and behavioural dimensions.
Keywords: inter-ethnic relations; minority-minority relationship; social distance; ethnic minority